Acid sphingomyelinase as target of Lycium Chinense: promising new action for cell health. Issue 1 (December 2016) - Ceccarini, Maria; Codini, Michela; Cataldi, Samuela; Vannini, Samuele; Lazzarini, Andrea; Floridi, Alessandro; Moretti, Massimo; Villarini, Milena; Fioretti, Bernard; Beccari, Tommaso; Albi, Elisabetta
Abstract Background Sphingomyelin plays very important roles in cell function under physiological and pathological conditions. Physical and chemical stimuli produce reactive oxygen species that stimulate acid sphingomyelinase to induce apoptosis. Antioxidant plants of the traditional Chinese Pharmacopoeia, such asLycium Barbarum andLycium Chinense, have become increasingly popular in Western countries. We investigated the effects ofLycium Chinense on acid sphingomyelinase and sphingomyelin species in relation to gene expression. Methods We preparedLycium Chinense berry extracts and evaluated their antioxidant properties. Increasing amount of extracts was used to test cytotoxic and genotoxic effect on HepG2 cells. Gene expression, protein amount and enzyme activity of acid sphingomyelinase were tested by RT-PCR, immunoblotting and enzymatic activity assay, respectively. Sphingomyelin species were analyzed by UFLC MS/MS. A panel of 96 genes involved in oxidative stress, proliferation, apoptosis and cancer was used to test the effect of LC on gene expression. GLRX2, RNF7, and PTGS1 proteins were analyzed by immunoblotting. Results We showed thatLycium Chinense berries have high antioxidant properties, have an IC50value of 9.55 mg/mL, do not induce genotoxic effect and maintain high level of cell viability. The berry extracts inhibit acid sphingomyelinase activity and increase both very long fatty acid sphingomyelin species and unsaturated fatty acid sphingomyelin species. Among 96 genes, Lycium Chinense berries up-regulate Glutaredoxin 2 and Ring Finger Protein 7 genes and proteins, able to protect cells from apoptosis. Intrigantly, Lycium Chinense berries down-regulates Prostaglandin H synthase 1 gene but the protein is not expressed in HepG2 cells. Conclusion The results identify acid sphingomyelinase as a novel target ofLycium Chinense berries to decrease saturated/unsaturated fatty acid sphingomyelin ratio, known to be useful for cell health. Consistent with these data, the berries regulate specifically gene expression to protect cells from apoptosis.